Experts Examine Recent Developments in Interventional Cardiology - Cunningham, Muriel (MD Conference Express, 2015)
Experts reviewed current issues in interventional cardiology. This review included the present state of transcatheter valve implantation and repair, the optimal duration of dual antiplatelet therapy after percutaneous coronary intervention, whether or not to treat nonculprit coronary artery disease during the index percutaneous coronary intervention in patients with STEMI, and clinical trials of renal denervation.